Respuesta :

For this case we must rewrite the equation in standard form:

[tex]Ax + By = C[/tex]

We manipulate the given equation algebraically:

[tex]y-3 = 4x-4[/tex]

We subtract [tex]4x[/tex] on both sides of the equation:

[tex]-4x + y-3 = -4[/tex]

We add 3 to both sides of the equation:

[tex]-4x + y = -4 + 3[/tex]

Different signs are subtracted and the major's sign is placed:

[tex]-4x + y = -1[/tex]

We multiply by -1 on both sides of the equation:

[tex]4x-y = 1[/tex]

Finally, the equation in standard form is:

[tex]4x-y = 1[/tex]

Answer:

[tex]4x-y = 1[/tex]